Understanding E-Democracy Government-Led Initiatives for Democratic Reform - Freeman, Julie; Quirke, Sharna (JeDEM - eJournal of eDemocracy and Open Government, 2013)
Information and communication technologies (ICTs) offer opportunities for greater civic participation in democratic reform. Government ICT use has, however, predominantly been associated with e-government applications that focus on one-way information provision and service delivery. This article distinguishes between e-government and processes of e-democracy, which facilitate active civic engagement through two-way, ongoing dialogue. It draws from participation initiatives undertaken in two case studies. The first highlights efforts to increase youth political engagement in the local government area of Milton Keynes in the United Kingdom. The second is Iceland’s constitutional crowdsourcing, an initiative intended to increase civic input into constitutional reform. These examples illustrate that, in order to maintain legitimacy in the networked environment, a change in governmental culture is required to enable open and responsive e-democracy practices. When coupled with traditional participation methods, processes of e-democracy facilitate widespread opportunities for civic involvement and indicate that digital practices should not be separated from the everyday operations of government. While online democratic engagement is a slowly evolving process, initial steps are being undertaken by governments that enable e-participation to shape democratic reform.